Nutritional Value and Quality Profile of Fresh Rabbit Meat in Assiut City, Egypt - *, sherief (International Journal For Research In Agricultural And Food Science, 2018)
Nutritional value and safety have gained great importance among the factors that determine meat quality. In the present study thirty rabbits were randomly bought from retail rabbit slaughterhouses in Assiut city, Egypt. They were slaughtered and divided into two halves and each half was further subdivided into fore and hind quarter for chemical and microbiological assessments. The samples were assessed chemically for the proximate composition (moisture, protein, fat, carbohydrate and gross energy content), thiobarbituric acid reactive substances (TBA), total cholesterol (Chol), triglycerides (Trigl), high-density lipoprotein (HDL) cholesterol and low-density lipoptotein (LDL) cholesterol. For microbiological assessment the total aerobes, Enterobacteriaceae, E.coli, Staphylocooccus aureus, mold and yeast counts (cfu/ml) as well as incidence of Salmonella spp were assessed in the rinse of the fore and hind quarters. The mean values of moisture, protein, fat, ash, and carbohydrate were 75.2±0.48 and 76.13±0.26; 19.81±0.22 and 20.59±0.18; 3.54±2.39 and 1.78±0.19; 1.12±0.03 and 1.17±0.03; and 0.33±0.03 and 0.33±0.03 for fore and hind quarter samples, respectively. The protein and fat means were significantly different (P<0.05), while those for moisture, ash and carbohydrate were not (P>0.05). The gross energy (Kcal/100g) mean values were 112.42±4.04 and 99.67±1.82, respectively, and the TBA (mg malonaldehyde/kg flesh) values were 0.3±0.03 and 0.19±0.02, respectively, with a significant difference (P<0.05). For Chol, Trigl, HDL, and LDL, the mean values were 59.13±4.4 and 54.97±3.9; 19.04±1.56 and 25.9±2.77; 22.36±1.17 and 21.95±1.47; and 32.96±4.4 and 27.85±3.74 mg/100g, respectively. No significant difference (P>0.05) was observed for Chol, HDL, and LDL means value. The LDL % was higher in fore (49.11±3.58) than in hind (46.33±3.37) quarter samples. The mean value of total aerobes, Enterobacteriaceae, Staphylococcus aureus, and mold and yeast counts for positive samples were 2.7±0.82 x106 and 4.2±1.57 x106; 3.56±2.10 x105 and 9.53±4.97 x105; 3.63±2.48 x105 and 1.59±1.53 x105; 1.29±1.25 x105 and 1.25±0.84 x105; and 3.2±0.98 x106 and 4.6±1.95 x106 cfu/ml, respectively. No significant difference for the previous counts between fore and hind quarters was found. E.coli couldn’t be detected in any of the fore quarter samples, but it in only one hind quarter sample with a count of 5x102 cfu/ml. Salmonella spp were detected in percentage of 23.3 and 20% in fore and hind quarter samples, respectively. It could be concluded that nutritional properties of fresh rabbit meat is healthier over other meats (high in protein and low in fat). Hind quarters meat was found to be superior to fore quarters from the nutritional and public health points of views (higher in protein, lower in fat, Chol, LDL%, and TBA as well in incidence of salmonellae).